ANLISIS MODEL BISNIS SISTEM E-PROCURERMENT TANDAN BUAH SEGAR (TBS) SAWIT PETANI SWADAYA UNTUK MENDUKUNG PROGRAM PENGEMBANGAN BIODIESEL - Kursehi Falgenti (INTI Nusa Mandiri, 2021)
The biodiesel biofuel conversion program requires more Crude Palm Oil (CPO) to produce environmentally friendly fuels. Fresh Fruit Bunches (FFB) from independent smallholders' oil palm lands are relied on to meet CPO needs. To ensure independent smallholders 'palm fruit is actually used in the biodiesel and green fuel program, it is necessary to carry out a digital transformation in the procurement of independent smallholders' FFB by building an integrated e-procurement system makes it easier for DPDPKS to monitor the procurement of FFB by cooperatives and the production of CPO by PKS as raw material for biodiesel. This study aims to analyze the business processes of independent smallholders' FFB procurement to design an integrated independent smallholder FFB e-procurement system, ensuring that CPO production for biodiesel comes from independent smallholder oil palm lands. E-procurement also integrates the FFB harvest schedule managed by the cooperative and the CPO production schedule created by the Palm Oil Mill (PKS). This e-procurement will facilitate the coordination of FFB procurement between PKS and cooperatives and between cooperatives and independent smallholders. This e-procurement is supported by cloud computing technology, allows realtime services to be accessed anytime and anywhere. All procurement activities are recorded in the cloud servicse so that the amount of FFB supply from independent farmers for biodiesel can be monitored as well as downstream biodiesel shipments can be monitored ensuring subsidies for biodiesel distribution are right on target.